Boundaries : how the Mason-Dixon line settled a family feud & divided a nation - Walker, Sally M. (Candlewick Press, 2014)
Traces the history of the Mason-Dixon Line as reflected by family feuds, exploration, scientific advancement and the cultural conflicts between America's northern and southern states.